Toxicity and efficacy of Gamma Knife radiosurgery for brain metastases in melanoma patients treated with immunotherapy or targeted therapy—A retrospective cohort study. (6th April 2020) - Gatterbauer, Brigitte; Hirschmann, Dorian; Eberherr, Nadine; Untersteiner, Helena; Cho, Anna; Shaltout, Abdallah; Göbl, Philipp; Fitschek, Fabian; Dorfer, Christian; Wolfsberger, Stefan; Kasprian, Gregor; Höller, Christoph; et al.
Abstract: Background: Few safety data of concurrent stereotactic radiosurgery and targeted therapy (TT) or immunotherapy (IT) are available. The aim of the study was to evaluate the outcome of melanoma patients with brain metastases (MBM) after Gamma Knife Radiosurgery (GKRS) in relation to IT/TT. Methods: We evaluated 182 MBM patients, who were treated with GKRS in the modern radiosurgical and oncological era. Results: The median time between the initial melanoma diagnosis and occurrence of MBM was 2.4 years. The median overall survival time was 5.4 years after melanoma diagnosis. The estimated median survival after the initial diagnosis of MBM was 1.0 year (95% CI = 0.7‐1.2 years). Patients treated with anti‐PD‐1 or a combination of anti‐CTLA‐4/PD‐1 showed a significantly longer survival after first GKRS compared to all other forms of treatment. In addition, patients treated with anti‐PD‐1, anti‐CTLA‐4, or a combination of anti‐CTLA‐4/PD‐1 showed a significantly longer time to new MBM after GKRS1 compared to patients treated with other forms and combinations of the oncological therapy. The occurrence of hemorrhage or radiation reaction/necrosis after GKRS did not show any statistically significant differences in relation to IT/TT. Conclusion: In MBM patients, complications after GKRS are not significantly increased if IT/TT treatment is performed at the time of or after radiosurgery. Further, a clear benefit in distant control and survival is seen in MBM patients treated with GKRS and checkpoint inhibitors. Thus, concomitant treatment of MBM with GKRS and IT/TT seems to be a safe and powerful treatment option although further prospective studies should be conducted. Abstract : In melanoma brain metastases patients, complications after GKRS are not significantly increased if IT/TT treatment is performed at the time of or after radiosurgery, and a clear benefit in distant control and survival is seen. Thus, concomitant treatment of MBM with GKRS and IT/TT seems to be a safe and powerful treatment option.